Pattern and Severity of Pulmonary Function Impairment in Patients with Post Tuberculosis Lung Disease (Medical Forum Monthly, 2026)
Objective: To determine the pattern and severity of pulmonary function impairment in patients with post-tuberculosis lung disease.Study Design: Descriptive cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Pulmonology, Liaquat University of Medical and Health Sciences, Jamshoro, from Dec 2022 to Jan 2024.Methods: The patients were selected using non-probability consecutive sampling, totalling 185 patients who had previously undergone anti-tuberculous (AT) therapy for pulmonary tuberculosis for at least six months. A structured proforma was used for the collection of demographic and clinical data. Spirometry was performed to determine pulmonary function, and ventilatory patterns were classified as obstructive, restrictive, mixed or normal.Results: Mean age of the patients 43.7 ± 12.5 years and 112 (60.5%) were male. Forty-nine (29.5%) patients had pulmonary function abnormalities and 36 (19.5%) had normal pulmonary function. The most common spirometric pattern was the obstructive ventilatory defect, seen in 72 (38.9%) patients, followed by the restrictive defect, seen in 49 (26.5%) patients and the mixed ventilatory defect, seen in 28 (15.1%) patients. The majority of severity were moderate pulmonary impairment. There was significant association between smoking history, recurrent tuberculosis and extensive radiological fibrosis with the presence of abnormal pulmonary function (p<0.05). Mean FEV1 values were significantly lower among smokers compared to non-smokers (58.4 ± 14.7% vs 66.9 ± 13.2%, p=0.003).Conclusion: Pulmonary function impairment is very common in patients with PBLD, and is most commonly characterized by an obstructive ventilatory defect. The impairment is worsened by smoking, recurrent TB and fibrotic lung changes. The post-tuberculous management should include routine spirometric assessment and longterm respiratory follow up for early diagnosis and treatment of chronic pulmonary sequels.